Biosorpsi BOD Dan TSS Limbah Laundri Oleh Tanaman Eceng Gondok (Eichhornia crassipes) - Vera Viena Vera Viena (Jurnal Serambi Engineering, 2016)
The research to assess the use of water hyacinth Eichhornia crassipes in biosorption process to remove BOD and TSS contents of laundri wastewater has been conducted. The research has 3 steps, e.i: (1) Preparation: water hyacinth cultivation in variated laundri wastewater 25%, 50% and 100% v/v, and wastewater analysis before process, e.i BOD, TSS, and pH; (2) Field test: cultivation of acclimatized water hyacinth in laundri wastewater with variation of surface coverage of 25%, 50% and 100% of total area; (3) Analysis of BOD, TSS in wastewater to account the biosorption eficiency. Results showed that water hycinth cultivation for 6 days gave the highest BOD (Biochemical Oxygen Demand) biosorption eficiency of 95,98%, which decreased from 544 mg/L to 21,85 mg/L value at total 100% area coverage. Water hyacinth also able to biosorp TSS (Total Suspended Solids) of 79,36%, which decreased from 218,00 mg/L to 44,99 mg/l value at total 100% area coverage. These BOD and TSS removals was affected by the organic metabolism and water hyacinth photosyntesis that made the laundri wastewater save for discarded to waterbody